Between Signsystems and Affects - Sjöholm, Cecilia (The Nordic Journal of Aesthetics, 2014)
Gotthold Ephraim Lessing’s Laocoon (1766) saw that the signification of art cannot be dissociated from its media. A visual work of art and a literary work originates in different spatial and temporal conditions, Lessing argued, serving thereby to liberate art from the tradition of ut pictura poesis. Lessing’s impact has been discussed in the tradition of modernism through Babbitt, Eisenstein and Greenberg, and there been associated with the notion that the work of art is autonomous. In Lessing’s own text, however, there is no clear conception of a work of art “an sich”. Instead, the work of art is characterized in an indirect manner, through the sense perception of the reader or viewer. Lessing’s Laocoon can be rethought from the perspective of affect. In his text, the human body has a central place, and Lessing’s investigation into the signification of the Laocoon can be formulated as the question: How does the embodied mind respond to the image of a human body? Departing from this concern, Lessing’s text does not only look at the object of aesthetics; it constructs an aesthetic subject, in which the embodied conditioning of sense perception and the question of affect is central. Making the statue of Laocoon a primary example in his study, Lessing inserts himself in a long tradition of the study of affects where Laocoon represents the most pain that a human can bear, whether that pain is corporeal or emotional.